2023
DOI: 10.3389/fmed.2023.1301822
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria in the regulation of ferroptosis and disease

Cheng Fu,
Nan Cao,
Sen Zeng
et al.

Abstract: Ferroptosis is a distinctive form of iron-dependent cell death characterized by significant ultrastructural changes in mitochondria. Given the crucial involvement of mitochondria in various cellular processes such as reactive oxygen species production, energy metabolism, redox status, and iron metabolism, mounting evidence suggests a vital role of mitochondria in the regulation and execution of ferroptosis. Furthermore, there exists a strong correlation between ferroptosis and various diseases. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…In the context of human pancreatic cancer cells, intriguing insights into the promotion of ferroptosis have emerged, particularly involving the endoplasmic reticulum protein stimulator of interferon genes (STING1) [ 44 ]. It has been observed that STING1 accumulates within mitochondria, where it engages with the mitochondrial outer membrane proteins mitofusins (MFN1/2) [ 44 ].…”
Section: Ferroptosis Implication In Cardiac Myocytes and Cardiovascul...mentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of human pancreatic cancer cells, intriguing insights into the promotion of ferroptosis have emerged, particularly involving the endoplasmic reticulum protein stimulator of interferon genes (STING1) [ 44 ]. It has been observed that STING1 accumulates within mitochondria, where it engages with the mitochondrial outer membrane proteins mitofusins (MFN1/2) [ 44 ].…”
Section: Ferroptosis Implication In Cardiac Myocytes and Cardiovascul...mentioning
confidence: 99%
“…In the context of human pancreatic cancer cells, intriguing insights into the promotion of ferroptosis have emerged, particularly involving the endoplasmic reticulum protein stimulator of interferon genes (STING1) [ 44 ]. It has been observed that STING1 accumulates within mitochondria, where it engages with the mitochondrial outer membrane proteins mitofusins (MFN1/2) [ 44 ]. This interaction instigates mitochondrial fusion, leading to the generation of reactive oxygen species (ROS) and subsequent lipid peroxidation, ultimately culminating in the initiation of ferroptosis [ 44 ].…”
Section: Ferroptosis Implication In Cardiac Myocytes and Cardiovascul...mentioning
confidence: 99%
See 3 more Smart Citations